Design and synthesis of [1, 2, 4]-triazolo isoquinoline derivatives via 1, 3-dipolar [3 + 2] cycloaddition: Reaction of azomethine imine with ethyl cyanoformate as unknown protocol. Issue 7 (14th February 2019) - Swapnaja, K. Jones M.; Yennam, Satyanarayana; Chavali, Murthy
Graphical abstract: Highlights: 1, 3-Dipolar cycloaddition of azomethine imine with ethyl cyanoformate is an extremely versatile atom economic process. Formation of triazolo isoquinoline moiety through 1, 3-dipolar cycloaddition of azomethine imines. Improved approach of 1, 3-dipolar cycloaddition of azomethine imine with electron rich cyanide group. Five member triazole fused isoquinoline building blocks for a variety of biologically active molecules. Abstract: A series of novel 1, 2, 4-triazolo isoquinoline derivatives(8a-8p) were synthesized starting from 2-phenylethan-1-ol derivative (1) in a7 step synthetic sequence. The key step in the scheme involves 1, 3-dipolar [3 + 2] cycloaddition of azomethine imine and ethyl cyanoformate as unknown reaction protocol. We have demonstrated the hydrolysis of both ester and benzoyl group in a single step and the corresponding carboxylic acid derivatives were coupled with various amines to generate unknown 1, 2, 4-triazolo isoquinoline derivatives The structures of the compounds(8a-8p) were characterized by 1 H NMR, 13 C NMR and HRMS analysis.